Managerial Roles: Intuitions of the Academic Institution Employees, an evidence from the universities in Ozamiz City - Anna C. Bocar (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2020)
Within this study, we want to determine the extent of academic administrators' managerial roles in a certain university, because their role in any academic institution is the most significance to lead the employees and middle managers. Once the administrators do the proper and appropriate management, the organization's goals will be attained. We employed the descriptive survey method, and used the rating of administration's managerial roles implementation, as one of our measures in our questionnaires. We formulated a qualitative scale, and each one has its corresponding verbal interpretation. In addition, we propose a hypothetical mean range, which is the assigned numeric value to strengthen and validate each of the particular qualitative extent. We found that the academic administrators manifested their managerial roles are at a great degree; confirming the interview with the nonteaching staff and the academic administrators themselves. We conclude that although the academic administrators manifested their capabilities in performing their managerial roles to attain the goals of the university, still, there were certain areas that they needed to develop, such as to enhance network with other institutions and community agency, to confine subordinate's workload with a dedication for official duties.